EFFECT OF Solanum nigrum AND Emblica officinalis FRUIT EXTRACTS AGAINST H2O2 INDUCED OXIDATIVE STRESS IN Saccharomyces cerevisiae - NAGESHWARI KRISHNAMURTHY; MANI ARUNKUMAR; BALAKUMAR SRINIVASAN; SIVAKUMAR RAMALAINGAM (International Journal of Pharma and Bio Sciences, 2013)
In this study, the effect of Emblica officinalis and Solanum nigrum fruit extracts against H2O2 induced oxidative stress in Saccharomyces cerevisiae was analyzed using vitamin E as standard. GC-MS analysis of ethanolic extract of S.nigrum and E.officinalis fruits revealed the presence of 51 and 25 phytoconstituents respectively. S.cerevisiae cells cultured in YEPD medium were divided into eight groups of 1X106 cells / ml each. The groups pre-treated with plant extract were subjected to oxidative stress by H2O2. Decreased apoptosis was observed with the yeast cells treated with fruit extract as compared with the cells treated with H2O2 alone. Antioxidant nature of the fruit extracts was determined by assessing SOD and catalase activity in yeast cells. The level of protein, SOD and catalase activity showed significant increase in yeast cells treated with plant extract than H2O2 treated cells. These extracts also protected the cells, its protein and other biomolecules from the oxidative damage, thereby increased the cell viability and stability. The protective mechanism may be due to the phytoconstituents with antioxidant nature and hence these plant fruits could be used as an alternate as therapeutic agents in free radical mediated diseases.